165k views
3 votes
Rhett is solving the quadratic equation zero equals X2 minus 2X -3 using the quadratic formula which shows the correct substitution of the value of a a,b and c into the quadratic formula

User Cuong Lam
by
6.0k points

1 Answer

6 votes
x^2-2x -3 =0
a =1 b =-2 and c = -3

x = - (-2) +/- sqrt (-2)^2 - 4(1)(-3)
--------------------------------------
2(1)

x = + 2 +/- sqrt [(4) - 4(-3)]
-------------------------------
2

x = +2 +/- sqrt [4 + 12]
--------------------------
2
x = +2 +/- sqrt[16]
-------------------
2

x = +2 +/- (4)
-------------
2

x = 2 + 4 or 2 -4
------- ------
2 2

x = 6/2 or -2/2

x = 3 or x = -1
User Clauub
by
5.9k points